Development Legal Theory and Progressive Legal Theory: A Review, In Indonesia’s Contemporary Legal Reform - Herlindah; Yadi Darmawan (Peradaban Journal of Law and Society, 2022)
The development legal theory and progressive legal theory are legal theories that are widely known in Indonesia. Both of them have inspired many legal experts and legal actors in Indonesia. The slow pace of legal reform in Indonesia, especially in eradicating corruption, is a big challenge that this nation must face. Therefore, the contribution of various parties is needed to answer the challenge. This article attempts to review the development legal theory and progressive legal theory in the context of legal reform in Indonesia. The study finds that both theories are very relevant to the current development of law in Indonesia. From the perspective of development legal theory, legal reform must be carried out by formulating laws that can encourage community transformation. On the other hand, the progressive legal theory emphasizes reforms in legal institutions and individual law enforcers. The law must be carried out by actors who have integrity and dare to take methods of a legal settlement that are out of the ordinary while remaining oriented and committed to the values ​​of justice and humanity.